2013 10th International Conference on the European Energy Market (EEM) 2013
DOI: 10.1109/eem.2013.6607308
|View full text |Cite
|
Sign up to set email alerts
|

Multi-national transmission planning using joint and disjoint solutions

Abstract: Abstract-Transmission systems have a critical role in wellfunctioning of liberalised electricity markets. Diversity in generation portfolio and improving system reliability are the main incentives for significant cross-border trades between Transmission System Operators (TSOs) in Europe. Nowadays, two ways are discussed for investment in additional transmission capacity by multiple TSOs: (1) Cooperative approach and (2) non-cooperative approache. In cooperative planning, the governing body looks for the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In our numerical study, we have analyzed an illustrative two-region network and a larger and more general three-region system. The two-region network results intuitively analyzed and validated our incentive mechanism approach, which includes a TPC, compared to the game-theoretic Nash equilibrium approach that does not have a TPC [13,11,15]. We showed that our proposed incentive mechanism indeed reached the Pareto optimal solution which is also the socially optimal solution.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In our numerical study, we have analyzed an illustrative two-region network and a larger and more general three-region system. The two-region network results intuitively analyzed and validated our incentive mechanism approach, which includes a TPC, compared to the game-theoretic Nash equilibrium approach that does not have a TPC [13,11,15]. We showed that our proposed incentive mechanism indeed reached the Pareto optimal solution which is also the socially optimal solution.…”
Section: Discussionmentioning
confidence: 79%
“…The authors have studied the impact of this free-riding on congestion revenues. In the reference [13], the authors have tried to improve the social welfare as presented in [11] by adopting different solution approaches, whereas in [14], the multi-regional transmission planing has been explored in the presence of wind generation and its associated uncertainty. References [15], [16], and [17] have explored the transmission expansion planning in the presence of generation expansion planning considering proactive and reactive coordination methods.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…In our numerical study, we have analyzed an illustrative two-region network and a larger and more general three-region system. The two-region network results intuitively analyzed and validated our incentive mechanism approach, which includes a TPC, compared to the game-theoretic Nash equilibrium approach that does not have a TPC [31,32,36]. We showed that our proposed incentive mechanism indeed reached the Pareto optimal solution which is also the socially optimal solution.…”
Section: Discussionmentioning
confidence: 79%
“…The authors have studied the impact of this free-riding on congestion revenues. In the reference [31], the authors have tried to improve the social welfare as presented in [32] by adopting different solution approaches, whereas in [33], the multi-regional transmission planing has been explored in the presence of wind generation and its associated uncertainty. References [36], [34], and [35] have explored the transmission expansion planning in the presence of generation expansion planning considering proactive and reactive coordination methods.…”
Section: A Literature Reviewmentioning
confidence: 99%